Putative host-derived growth factors inducing colonization of Burkholderia gut symbiont in Riptortus pedestris insect. (March 2020) - Lee, Junbeom; Mao, Xinrui; Lee, You Seon; Lee, Dong Jung; Kim, Junghyun; Kim, Jiyeun Kate; Lee, Bok Luel
Abstract: It is questionable that how gut symbiont can be proliferated in the host symbiotic organs, such as host midgut region, which are known to be highly stressful and nutritional depleted conditions. Since Riptortus - Burkholderia symbiosis system is a good model to study this question, we hypothesized that Burkholderia symbiont will use host-derived bacterial growth factor(s) to colonize persistently in the host midgut 4 (M4) region, which is known as symbiotic organ. In this study, we observed that although gut-colonized symbiotic Burkholderia cells did not grow in the nutrient-limited media conditions, these symbionts were able to grow dose-dependent manner by addition of host naïve M4 lysate, supporting that host-derived growth factor molecule(s) may exist in the host M4 lysate. By further experiments, a host-derived growth factor(s) did not lose its biological activity in the conditions of high temperature, treatment of phenol-chloroform or ethyl alcohol precipitation, indicating that a growth factor molecule(s) is neither a protein nor a DNA. Also, based on the biochemical analyses data, molecular weight of the host-derived bacterial growth factor(s) was turned out to be less than 3 kDa molecular mass and to give the positive chemical response to the ninhydrin reagent on thin layer chromatography. Finally, we found that one specific peak showing ninhydrin positive signal was separated by gel filtration column and induced proliferative activity for Burkholderia gut symbiont cells. Highlights: Riptortus insect has nutrient source or growth factor molecule(s) for stable proliferation of gut symbiont. The M4 lysate of Riptortus host induces symbiotic Burkholderia cells growth in vitro. Host-derived molecule(s) is neither a protein nor a DNA. Putative growth factor(s) was separated by gel filtration columns. This study describes molecular cross-talks between the host insect and gut symbiont.